STS and Innovation: Building and Jumping Fences - Alan Irwin (Engaging Science, Technology, and Society, 2023)
In this short contribution, I reflect upon the thematic collection as a whole, returning in particular to the three original questions posed in the collection’s introduction. In conclusion, I argue that STS has a substantial heritage in researching and engaging with innovation. However, drawing inspiration from the contributions in this collection, now is the time to take the STS-innovation relationship even further forward.